Comprehensive industrial training kit: Enhancing the preparation of industrial training report among students / Izzatil Husna Arshad ...[et al.] - Arshad, Izzatil Husna; Alias, Noor Rahmawat; Chik, Nor Kamariah; Hamidon, Huda; Abdul Hamid, Haslinda (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2017)
Faculty of Information Management prepares its final semester undergraduate students for the industrial training period of five months, involving 480-hour equivalent work placement, paid or unpaid, located in an approved industrial site, working under the supervision of experienced Information Professionals. During the industrial training period, the students are expected to contribute to the activities of the workplace and to meet the same demands of work production and responsibility expected by the organization of its regular employees. After completion of the industrial training, students are required to present and submit a report regarding activities and projects involved. To date, there are no comprehensive guidelines and standards in the Faculty of Information Management, Universiti Teknologi MARA to assist student's industrial training preparation, presentation and report documentation. Therefore, this study intends to identify the awareness of students towards the existence of industrial training guideline and their expectations. A survey has been conducted on 213 students (131 female, 82 male) from the Bachelor of Information Science (Hons) Information Systems Management (IM245), final year bachelor programme, at the Universiti Teknologi MARA Cawangan Kelantan. The findings show that comprehensive and standardized guideline is needed by the students to guide them in writing a good industrial training report. This study also significantly contributes in producing a comprehensive all-in-one booklet which is known as Industrial Training Kit (IT Kit) that contains all forms and guidelines, including terms and conditions, rules and regulations provided by the Ministry of Higher Education (MOHE) and Faculty of Information Management. This comprehensive training kit could also be used as a guideline to assist various faculties in managing their students' practical training